Izstreljevanje namiznoteniške žogice s pomočjo vodnega topa - Šantej, Jure (Fizika v šoli, 2024)
The paper introduces a problem investigation of launching a ping pong ball using a water cannon, which is this year's problem at YPT. The objective is to optimise the launching mechanism to achieve the maximum final height. We explain how capillary forces affect the ball launch and the composition of the experimental enviroment. In the process, we enhanced our measuring and data analysis techniques using the Tracker computer programme. The results show that the ball will reach its maximum height in a medium-diameter container released from the highest launch position.
Keywords: eksperimenti; fizika; kapilarne sile; turnir mladih fizikov; vodni top